Laplace plane GeoSAR feasibility study: summary of the group design project MSc in astronautics and space engineering 2014-15, Cranfield University - Hobbs, Stephen (Cranfield University, 2015)
Students of the MSc course in Astronautics and Space Engineering 2014-15 at Cranfield University performed a feasibility study of a geosynchronous radar mission for their group project. This report summarises the students' work and their findings. The report consists of an overview and discussion of the technical work of the project and a compilation of the executive summaries which describe the special contributions of each student. The mission studied is a geosynchronous synthetic aperture radar Earth observation mission using the Laplace orbit plane to reduce station-keeping propulsion demand. User applications are drawn from a wide range of sectors (agriculture, meteorology, geohazards, etc.) and are translated into system design requirements. The proposed mission design uses satellites with 13 m diameter antennas and a total electrical power demand of 6 kW. The mission seems feasible, although further study is recommended especially for the areas of _ orbit selection with respect to user requirements, imaging performance and orbit maintenance, _ mass budget (driven largely by the propulsion system), _ user requirements, imaging performance and operational imaging modes, _ opportunities for improved imaging with a constellation.